Self-Concept in Students' Premarital Sexual Behavior Experiences - Rini Subekti; Chr. Argo Widiharto; Yunita Dwi Setyoningsih (Universitas PGRI Yogyakarta, 2026)
Although there are prohibitions of legal and religious norms related to premarital sexual behavior, the fact is that in Indonesia, it is currently something commonplace among teenagers and adults. However, little is known about how college students who engage in premarital sexual behavior perceive themselves. This study uses a qualitative phenomenological approach, interpretative phenomenological analysis (IPA). Research that emphasizes results in written form and in the words of the individuals being observed to understand aspects of life and to find the essence of individuals' experiences of similar phenomena. This study involved three 22-year-old female students who had engaged in premarital sexual behavior with their boyfriends, were selected by purposive sampling, and were willing to fill out informed consent. The findings showed that the participants' self-concept was positive. Comfort and permissive environment are the main factors that affect the participants' premarital sexual behavior which then shifts the participant's ideal self who initially has a self-image of obedience to the norm, which causes the emergence of a misalignment between the real self and the ideal self which causes incongruence of the participants which then gives rise to inferiority and affects self-esteem and produces a process of reconstruction of self-meaning that ultimately forms the concept of self. These findings underscore the need for preventive services for risky sexual behavior to help students and students minimize premarital sexual behavior by strengthening social norms through an empathetic approach and not judging. Keywords: self-concept, premarital sexual, students